A compact triple band notch circular ring antenna for UWB applications. Issue 3 (March 2015) - Srivastava, Gunjan; Dwari, Santanu; Kanaujia, Binod Kumar
ABSTRACT In this article, a study of a triple band notched circular ring monopole ultrawide band (UWB) antenna is presented. The UWB antenna consists of a circular ring radiating patch and rectangular ground plane with two small slots near the feed line for bandwidth enhancement. The proposed antenna can reject worldwide interoperability for microwave access (WiMAX) band (3.3–3.8 GHz), wireless local area network (WLAN) band (5–6 GHz) and X‐band downlink satellite communication band (7.1–7.9 GHz). The WiMAX and WLAN band rejections are realized by introducing two arc shaped elliptical slots and single elliptical split ring slot in the radiating patch, respectively. Furthermore, a pair of rectangular single split ring resonators is used to obtain the rejection of X‐band downlink satellite communication signal. The proposed UWB antenna is fabricated and measured. The measured results are in good agreement with the simulated ones. © 2015 Wiley Periodicals, Inc. Microwave Opt Technol Lett 57:668–672, 2015